2003
DOI: 10.1021/jp027361g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Uptake of PAHs by Organic-Coated Aqueous Surfaces

Abstract: We report direct laser-induced fluorescence measurements of the uptake of the polycyclic aromatic hydrocarbons (PAHs) anthracene and pyrene to the air−aqueous interface for pure water and for water coated with an organic film. The surface uptake coefficients of anthracene and pyrene to the air−water interface are estimated to be on the order of 10-5. For both PAHs, the surface uptake coefficients for uptake to a 1-octanol-coated water surface increase by a factor of 2−3 over those determined for the pure water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
82
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 33 publications
12
82
1
Order By: Relevance
“…This is an upper limit for the surface coverage in our experiments, as equilibrium conditions had not been reached after 15 min of deposition, at which time we still observed a linear increase in phenanthrene fluorescence at the air-ice interface. As discussed in Mmereki et al [35], this suggests that the experiments reported here were done in the unsaturated regime of phenanthrene surface coverage. On organic films [30], rates of anthracene ozonation are independent of surface coverage within a submonolayer regime.…”
Section: Ozonation Kinetics Of Phenanthrene On Water and Icesupporting
confidence: 52%
“…This is an upper limit for the surface coverage in our experiments, as equilibrium conditions had not been reached after 15 min of deposition, at which time we still observed a linear increase in phenanthrene fluorescence at the air-ice interface. As discussed in Mmereki et al [35], this suggests that the experiments reported here were done in the unsaturated regime of phenanthrene surface coverage. On organic films [30], rates of anthracene ozonation are independent of surface coverage within a submonolayer regime.…”
Section: Ozonation Kinetics Of Phenanthrene On Water and Icesupporting
confidence: 52%
“…The simulations in which the impinging water molecules became entrained within the monolayer were extended for an additional 125 ps (to 200 ps), with no observable change in state. Studies have previously reported instances of organic films effectively acting as a solvent for other gas phase molecules [e.g., Mmereki et al, 2003]. The pair radial distribution functions between the oxygen atom of the entrained water molecule and atoms of the octanoic acid indicate that the water molecules preferentially lie near the hydrophilic head group of the amphiphile, which suggests an explanation for its apparent preference for adsorption rather than desorption (Figure 8).…”
Section: Takahama and Russell: Water Mass Accommodation On Films D022mentioning
confidence: 83%
“…The film coating can also act as a barrier to water uptake by and evaporation of the droplet and can inhibit the transport of various atmospheric species from the gas to the aqueous phase [6][7][8][9][10][11][12][13]. Conversely, the film can act as a "2D solvent" for atmospheric species that would not normally partition to the aqueous phase, or can alter the solvation behaviour of those that would [14][15][16][17][18]. Very recently, Forestieri et al [19] studied the surface tension effects on sea spray aerosol mimics (oleic, palmitic, myristic acids, and their mixtures) using a surface film model to establish the properties that surface-active organic molecules must have to substantially impact on the aerosol's activation efficiency.…”
Section: Introductionmentioning
confidence: 99%